A cost model of part consolidation for additive manufacturing - Stevenson, Alicia (2018)
Part consolidation (PC) is concerned with reducing the number of components in an assembly, and has long been the focus of traditional Design for Manufacture and Assembly guidelines to reduce assembly costs. However, the limitations of traditional processes and correlation between design complexity and cost more often results in products with multiple separate components and complex assembly requirements. Additive manufacturing (AM) processes build parts layer by layer meaning they are capable of manufacturing considerably more complex geometries and do not have the same complexity-cost correlation. PC is described throughout the literature as one of the major benefits of AM, with potential for reducing assembly requirements, reducing inventory and supply chain complexity, and improving product quality by reducing tolerance stack-up. However, there is currently very little empirical evidence provided or means to quantify the impact of PC on costs throughout a product’s lifecycle. This thesis presents an empirical based cost model developed to enable organisations to quantify the impacts of PC on costs for use during the pre-installation phase of AM adoption. The motivation behind this study is the lack of application of advanced manufacturing technology implementation research to AM adoption, and the inability of organisations to systematically consider the potential impact of PC on costs within the justification phase. A single company case study research approach has been used to develop the cost model, basing it on activities within the research host company. To trial the cost model, embedded redesign case studies were performed to investigate PC in isolation and base the model calculations on empirical evidence. The remaining parameters were defined based on data from the host company. The results show that AM has the potential to significantly reduce part count of sub-assemblies within the host company’s products by up to 96%, with a potential 86% cost saving. Contrary to DFMA rules, parts that need to move bodily with respect to other parts and that were originally separated for assembly of other components could both be consolidated using AM. The significant cost savings occur where numerous components are consolidated through PC, thereby eliminating considerable cost elements. This research indicates that the impact of PC on costs could have a significant impact on decisions made with regards to AM adoption, and could provide the justification for further investigation and investment to fully implement and benefit from the technology. To improve utilisation of the cost model, it was developed into an Excel-based tool enabling organisations to quickly adapt parameters to reflect their own business model and potential for PC based on redesign case studies. A practical approach based on the methodology used in this research is also developed to help organisations adapt and apply the PC cost model.